Analysis of the Mu'jamul 'Arabiyyah Lil Hayah Dictionary - Nur Azizah, Balkis (Assuthur: Jurnal Pendidikan Bahasa Arab, 2024)
Mu'jamul 'Arabiyyah lil Hayah is a dictionary compiled by UIN Malang language development to make it easier for students to learn Arabic. This dictionary is analyzed in terms of components, systematics and structure. This research aims to analyze Mu'jamul 'Arabiyyah lil Hayah as a whole, using descriptive qualitative research. The results of this research are that Mu'jamul 'Arabiyyah lil Hayah is an ideal dictionary because of its convenience, completeness, accuracy, it meets the learning criteria in language development at UIN Malang. Another researcher. Furthermore, it is hoped that we will be able to study and analyze more broadly the Mu'jamul 'Arabiyyah lil Hayah using other points of view.